Dynamic behaviour of pm traction machines during symmetrical short circuits - Eichin, Fabian (Stellenbosch : Stellenbosch University, 2025)
Eichin, F. 2025. Dynamic Behaviour of PM Traction Machines During Symmetrical Short Circuits. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/63a690f8-1e46-4ca1-aad0-108a1d43eeb4